My City Highrise Garden - Brownmiller, Susan (Book collections on Project MUSE., 2017)
Gardening on rooftops, balconies, and terraces is a popular trend. After thirty-five years of experience, Susan Brownmiller writes with honesty and humor about her oasis twenty floors above a Manhattan street. She reports the catastrophes: losing daytime access during building-wide renovations; assaults from a mockingbird during his mating season. And the joys: a peach tree fruited for fifteen years; the windswept birches lasted for twenty-five. Butterflies and bees pay annual visits. She pampers a buddleia, a honeysuckle, roses, hydrangeas, and more. Her adventures celebrate the tenacity of nature, inviting readers to marvel at her garden's resilience, and her own.